Risk Factors of Asthma among Adolescent and Adults: A Systematic Review Study and Meta-Analysis - Sri Iswahyuni; Rejo Rejo; Sri Sayekti Heni Sunaryanti; Asruria Sani Fajriah; Tri Yuniarti; Isnani Nurhayati (Journal of Epidemiology and Public Health, 2021)
Background: Asthma is a global public health problem that affects the quality of life of patients and is associated with the number of deaths each year. Factors such as genetics, environment and behavior are believed to have a significant relationship to the development of asthma. This study aimed to identify risk factors for asthma in adolescents and adults.Subjects and Method: This was a systematic review and meta-analysis with a search for articles published by the online database PubMed in 2016 to 2021. The dependent variable was asthma. The independent variables were several risk factors that influence diseases such as smoking, age, and others. Data were analyzed using RevMan software version 5.3.Results: A subgroup analysis was conducted from 4 articles which stated that cardiovascular related There were a total of 12 articles analyzed in this study. Subjects who had allergic rhinitis (OR= 3.80; 95% CI= 1.65 to 8.77; p= 0.001) had a greater risk of developing asthma than those who did not. This also applies to subjects who smoke (OR= 1.53; 95% CI= 1.32 to 1.78; p= 0.001), live in urban areas (OR= 1.46; 95% CI= 1.13 to 1.89; p= 0.03), are female. (OR= 1.19; 95% CI= 0.91 to 1.55; p= 0.001).Conclusion: Asthma is more susceptible to people who have allergic rhinitis, smoke, live in urban areas, are female.Keywords: asthma, prevalence, risk factors.Correspondence: